Pemahaman Pemangku Terhadap Fungsi Dan Makna Genta Di Desa Adat Tegal Darmasaba, Kecamatan Abiansemal, Kabupaten Badung - Ida Ayu Diah Larashanti; I Made Sukma Muniksu (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
The writing of this study aims to provide an explanation of the function and meaning of genta in the understanding of pemangku. This research is qualitative, qualitative research is a method used to examine the condition of objects that occur naturally. A sociological approach is used to examine the existence of genta in the form of their functions and meanings among pemangku. Furthermore, to complete this research data, collect data through observation, interviews and literature study. The function of the genta for pemangkus is as a concentration tool, namely in every activity carried out it is necessary to have concentration in physical and mental form. Genta is identified with ongkara which is a symbol of the great universal soul or Ida Sang Hyang Widhi Wasa in his full form which includes purusa and pradana, in other words genta is interpreted with the niyasa of Ida Sang Hyang Widhi Wasa. Keywords: Function and Meaning of Genta, Understanding of Pemangku